Der Mensch im Katastrophenuniversum. Zum Verhältnis von Historie, Naturgeschichte und Poetik im Frühwerk Arno Schmidts - Stepan Zbytovsky (Ecozon@, 2012)
Among the representations of nature in Arno Schmidt's early texts from the debut novel Leviathan towards his radio features, scenes of diverse loci terribiles and destructive forces of nature take a prominent place. In several texts, natural processes and disasters are described as trigger or executor of the apocalypse. In analogy with the dual significance of the term ‘natural catastrophe’, which refers to both the extreme natural event itself and its impact on culture and civilisation, Schmidt linked scientific data with mythological and other cultural patterns of interpretation in these passages. Starting from the concept of nature as Leviathan, Schmidt's understanding of nature is examined, and shown to be one in which natural disasters are understood not as contingent accidents, but as defining moments of natural history. These are closely interwoven by Schmidt with culture and human history, and mirrored in his poetological programme. This article focuses on the connections between the three components, in the context of Germans coming to terms with the past and the discourse of cultural ecology (especially A. Goodbody, H. Zapf).